The effects of cataract surgery on autonomic heart rate control: a prospective cross-sectional and analytical study - Aoki, Ricardo H.; Bezerra, Italla Maria Pinheiro; Almeida-júnior, Alvaro Dantas De; Barbosa, Renata Thaís De A.; Valenti, Vitor E.; Oliveira, Fernando R.; Roque, Adriano L.; Ferraz E Souza Júnior, Hugo Macedo; Garner, David M.; Raimundo, Rodrigo D.; Abreu, Luiz Carlos De (Faculdade de Medicina / USP, 2019)
OBJECTIVES: We aimed to evaluate the effects of cataract surgery on cardiac autonomic modulation.METHODS: A cross-sectional and analytical study was conducted at the Hospital Maria Braido in the city of São Caetano do Sul, São Paulo, between 2015 and 2016. We investigated 19 patients of both sexes who were all over 50 years old; all patients had a diagnosis of senile or bilateral cataracts and were recommended to undergo implantation of the intraocular lens. Heart rate variability (HRV) was evaluated before, during and after cataract surgery.RESULTS: There were no significant changes in the time and geometric domains of HRV before, during or after surgery. The high-frequency (HF) band in normalized units (nu) on the spectral analysis significantly increased (p=0.02, Cohen’s d=0.9, large effect size). However, the low-frequency (LF) band in nu significantly decreased during surgery (p=0.02, Cohen’s d=0.9, large effect size).CONCLUSION: Throughout the intraocular lens implantation cataract surgery, there was an increase in parasympathetic modulation and a decrease in the sympathetic component of the heart rate (HR). We propose that this result is attributable to the supine position of the patients during surgery and the trigeminal reflex.
Keywords: Autonomic Nervous System; Heart Rate Variability; Cardiovascular System; Cataract; Ophthalmologic Surgical Procedures